Evaluating Cost Center Managers through Accountability Accounting at PT Mayora Indah Tbk - Masnawaty Sangkala (PT. Maju Malaqbi Makkarana, 2026)
This study aims to evaluate cost-center managers through the implementation of accountability accounting at PT Mayora Indah Tbk. Accountability accounting is examined as a managerial control mechanism that links cost responsibility, budgeting, cost realization, and performance evaluation within an organizational responsibility structure. This study applies a descriptive qualitative method using secondary data obtained from the company’s financial statements and related financial information. The analysis focuses on the extent to which accountability accounting supports the assessment of cost-center managers by identifying controllable costs, comparing budgeted and actual costs, and evaluating cost variances. The findings indicate that accountability accounting plays an important role in strengthening cost control and managerial performance assessment. Although the company demonstrated positive revenue performance, increased operating costs affected the achievement of operating profit and net profit. This condition shows that financial performance cannot be assessed only from revenue growth, but must also consider the effectiveness of cost management. Therefore, accountability accounting provides a more objective basis for evaluating cost-center managers, particularly in monitoring cost efficiency and responsibility-based performance. The novelty of this study lies in positioning accountability accounting not merely as a financial reporting practice, but as a practical evaluation framework for cost-center managerial performance in a publicly listed manufacturing company.